Evaluation of secondary school geography teachers’ pedagogical practices in Southwestern Nigeria - Olayemi, Andrew A.; Amosun, Peter A. (Goodwood Publishing, 2024)
Purpose: This study was conducted to evaluate teachers’ pedagogical practices in secondary schools in southwestern Nigeria because evidence has shown that some of the objectives of the geography curriculum are hardly met. Research interest has been more on interventions, especially strategies to improve students’ learning outcomes in geography, than on the evaluation of implementation. Research methodology: A mixed-methods design was adopted. Three states (Osun, Oyo, and Ekiti) in southwestern Nigeria were randomly selected, and the purposive sampling technique was used to select schools with a geography teacher who was willing to participate in the study. Results: Most teachers (67.1%) deployed the lecture method, while schools (84.6%) had insufficient time to implement GC. Inadequate materials (84.1%), limited opportunities for professional development (89.4%), and insufficient allocated time (78.7%) were the major challenges associated with the implementation of GC. The pedagogical practices were good (????? = 3.40), but material resources were inadequate (????? 0.83), 3.4 against the threshold of 3.0 and 1.0, respectively. Contribution: Teachers rarely used the field-trip approach. The teachers posited that they had inadequate resources for implementation. School administrators should ensure that geography is allotted sufficient time to the timetable. Limitations: The observer effect may have slightly influenced the classroom activities of some teachers and students. Similarly, not all items on the rating scale could be captured extensively within the observed teaching-learning period. Novelty: Although the goals of sustainable development place a special emphasis on healthy and prosperous lives, insufficient data on mental health have been collected, and mental health policies based on village wisdom have not become a theme that many central and regional governments have implemented.